An inventory of human rights law relevant for surveyors - Molen, Paul van der (2020)
Within FIG, major guidance is provided on issues related to human rights, although often quite implicitly. The definition of a surveyor of 2004 includes -for example- a clear statement that surveyors should take into account the relevant legal, economic, environmental and social aspects affecting their work. As governments are obliged to translate the human rights treaties which they ratified into national legislation, the domestic human rights context is thus present. FIG also issued publications on subject-matters that have -one way or another- a relation with human rights. The starting point of these publications often is ‘good governance’ in general or ‘good land governance’ in particular. This is fine, as the source of many good governance principles are human rights. The main aim of this paper is to make an inventory of the body of human rights law which is relevant for surveyors and –as it were- to feed it explicitly into the fundament of the profession. A derived aim is to identify interfaces with the surveyor’s profession